Autonomous Navigation for an Unmanned Aerial Vehicle by the Decomposition Coordination Method - Chaimaa Jihane; Hala El Ouarrak; Mohamed Mestari; Mostafa Rachik (IAES Indonesia Section, 2017)
This paper introduces a new approach for solving the navigation problem of Unmanned Aerial Vehicles (UAV) by studying its rotational and translational dynamics and then solving the nonlinear model by the Decomposition Coordination method. The objective is to reach a destination goal by the mean of an autonomous computed optimal path calculated through optimal control sequence. Solving such complex systems often requires a great amount of computation. However, the approach considered herein is based on the Decomposition Coordination principle, which allows the nonlinearity to be treated at a local level, thus offering a low computing time. The stability of the method is discussed with sufficient conditions for convergence. A numerical application is given in consolidation the theoretical results.